Survival predictors of Burkitt's lymphoma in children, adults and elderly in the United States during 2000–2013. Issue 7 (9th January 2017) - Mukhtar, Fahad; Boffetta, Paolo; Risch, Harvey A.; Park, Jong Y.; Bubu, Omonigho M; Womack, Lindsay; Tran, Thuan V.; Zgibor, Janice C.; Luu, Hung N.
Abstract : Burkitt's Lymphoma (BL) has three peaks of occurrence, in children, adults and elderly, at 10, 40 and 70 years respectively. To the best of our knowledge, no study has been conducted to assess predictors of survival in the three age groups. We hypothesized that survival predictors may differ by age group. We, therefore, sought to determine survival predictors for BL in these three groups: children (<15 years of age), adults (40–70 years of age) and elderly (>70 years of age). Using the Surveillance, Epidemiology, and End Results (SEER) database covering the years 2000‐2013, we identified 797 children, 1, 994 adults and 757 elderly patients newly diagnosed with BL. We used adjusted Cox proportional hazards regression models to determine prognostic factors for survival for each age group. Five‐year relative survival in BL for children, adults and elderly were 90.4, 47.8 and 28.9%, respectively. Having at least Stage II disease and multiple primaries were associated with higher mortality in the elderly group. In adults, multiple primaries, Stage III or IV disease, African American race and bone marrow primary were associated with increased mortality whereas Stage IV disease and multiple primaries were associated with worse outcome in children. These findings demonstrate commonalities and differences in predictors of survival that may have implications for management of BL patients. Abstract : What's new? Occurrences of Burkitt's lymphoma peak around ages 10, 40 and 70. What factors predict survival at each age? These authors investigated, using data from the Surveillance, Epidemiology, and End Results (SEER) database in the United States. They determined five‐year relative survival rates of 90, 48 and 29% in children, adults and elderly patients, respectively. Some predictors of poor outcome were shared among all age groups, such as multiple primary tumor sites and advanced stage disease. Only in non‐elderly adults, African‐American race and bone marrow site of origin contributed to poor outcomes.